Size Effect in Lime-stone Calcined Clay Cement (LC3) incorporated Paver blocks: Mechanical and Durability Investigation - Yadav Amit; Kumar Rajesh; Khan Shahnavaz; Pippal Ashish; Khan Jeeshan (E3S Web of Conferences)
Limestone calcined clay cement (LC3) is a novel and environmentally friendly cement that is a blend of OPC clinker, calcined clay, limestone, and gypsum. Concrete paving blocks for footpaths and roads are favorable because of their ease of installation and improved appearance with a smooth surface. The incorporation of LC3 into paver blocks improves their quality while simultaneously being environmentally friendly. The present investigation deals with the analysis of different sizes of concrete pavement blocks of the M30 grade. This study aimed to investigate the effects of using LC3 with sand and quartz aggregates at aspect ratios of 1.5, 2.43, and 3.25. The mechanical and durability properties studied include tensile strength, flexural strength, compressive strength, and abrasion resistance. The strength parameters including the compressive strength and flexural strength of the paver blocks were determined to vary between 32.0-39.61 MPa and 5.5-8.6 MPa respectively. The tensile strength was in the lower range of 1.5-2.1 MPa. It was concluded that as the aspect ratio (length-to-thickness ratio of the pavers) was reduced, the strength attributes decreased. Thus, the incorporation of LC3 cement to develop paver blocks can be an environmentally friendly solution with a 40% reduction in CO2.